Combining decidability paradigms for existential rules. Theory and Practice of Logic Programming - CORRIGENDUM. Issue 1 (16th March 2015) - GOTTLOB, GEORG; MANNA, MARCO; PIERIS, ANDREAS
Abstract : Figure 3 was left out in the article (Gottlob et al.2013 ). The figure that is given there as figure 3 should in fact be figure 4. Further, the reference to figure 3 on the 4 th line of page 889 should be a reference to figure 4. The correct figure 3 (missing in the paper) is supplied below. We apologise for this error.